First Experience of Late Pruning on Kékfrankos Grapevine (Vitis vinifera L.) in Eger Wine Region (Hungary) - Szabolcs Villangó; András Szekeres; György Végvári; Gitta Ficzek; Gergely Simon; Zsolt Zsófi (Horticulturae)
Traditional winter pruning in dormancy (BBCH-00) as control (C) and three late pruning treatments, LP1 (wool stage—BBCH-05), LP2 (two leaves folded—BBCH-12), and LP3 (four leaves folded—BBCH-14), were applied on Kékfrankos grapevines. The evolution of the phenological growth stages, grape juice, wine analytical parameters, and phenolic composition were evaluated. The quantitative aspects of the grape berry, bunch, yield, and cane were also assessed. Our goal was to reach a decrease in sugar content and an increase in acidity. Delaying or postponing the phenological phases to bring technological and phenolic ripening closer together was also one of our objectives. These were accomplished, but the negative aspects of late pruning, which resulted in a reduction in the diameter and weight of the canes, should also be taken into account. We also found that, the later the late pruning, the more the yield was reduced. By postponing pruning, the phenological phases were also extended.